ENHANCED SENSITIVITY HIGH TEMPERATURE OPTICAL FIBER FPI SENSOR CREATED WITH THE CATASTROPHIC FUSE EFFECT - Domingues, M. F.
In this work, we describe a novel and cost effective approach based on optical fiber microcavities, for sensing high temperature values (up to 1150 degrees C). The proposed sensor is produced by splicing standard single mode optical fibers with fibers destroyed by the catastrophic fuse effect, resulting in a microcavity structure in the fiber core region. These microcavities have a thermal sensitivity of 10.43 +/- 0.15 pm degrees C-1, for temperatures up to 1150 degrees C, which compares well with the sensitivity of Fabry-Perot interferometric sensing cavities but with the advantage of substantially reduced manufacturing costs. (c) 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:972-974, 2015